Estudio Comparativo de Tres Estrategias de Control para la Regulaci´on de Frecuencia de una Micro Red en Operaci´on Aislada - Pineda Muñoz, Edwin Alexis; Gauthier Sellier, Alain (Ingeniería, 2020)
Context: The reduction of fossil fuels, the need to reduce emissions of carbon dioxide (CO2) on the planet and the interest in guaranteeing energy security have increased research in production of electrical energy using renewable energy sources incorporated into microgrids (MGs). This scenario presents technical challenges that must be covered to guarantee adequate levels of reliability. Method: This study compares three control strategies based on the predictive control of the model or MPC (Model Predictive Control), the optimal control LQ-Servo (Linear Quadratic Servo) and the control integral proportional or PI, with the aim of regulating the frequency against uncertainties in the load and environmental disturbances, considering an isolated linear microgrid model, which includes conventional and renewable generators, energy and load storage devices. Results: The simulations of the microgrid in isolated operation, in the presence of wind, load and solar power disturbances, show a better performance under different scenarios of the MPC and LQ-Servo controllers with respect to the dynamic characteristics presenting the frequency deviation and the control signal. Conclusions: The LQ-Servo optimal control strategy, little researched in microgrids, is presented as a viable option to consider in the design of secondary microgrid controllers in isolated operation, due to the characteristics of performance shown in the frequency regulation. Consideration of models that include restrictions in the control variables and in the states of the microgrid, as well as their implementation, remain for future work. Keywords: Cost function, renewable generation, optimization, disturbance, tuning. Language: Spanish.